Pelabelan Harmonis Ganjil Pada Graf Cm,n ⊵e C4 - Demetriana Kolo; Keristina Br. Ginting; Ganesha L Putra (JURNAL DIFERENSIAL, 2023)
Graph is an ordered pair of a vertex and edge set that related with various theories, one of them called labeling. There are a lot of types of graph labeling, one of them is odd harmonious labeling. The odd harmonious labeling is an injective function f : V (G) → {0, 1, 2, . . . , 2q − 1} such that induced a bijective function is f∗: E(G) → {1, 3, 5, · · · , 2q − 1} which is defined by f∗(uv) =f(u) + f(v). This study aims to construct an odd harmonious labeling on a graph Cm,n ⊵e C4. The results showed that a graph Cm,n ⊵e C4 is an odd harmonious graph.